The Effects of Environmental Risk on Consumption: an Empirical Analysis on the Mediterranean Countries - Donatella Baiardi; Matteo Manera; Mario Menegatti (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper empirically estimates a micro-founded model which studies the macroeconomic impact of environmental and financial risks on consumption choices in the Mediterranean Region. The analysis is carried out using time series aggregate data for fourteen Mediterranean countries over the period 1965-2008. Our results indicate that both risks and their interaction significantly influence consumption dynamics. Our estimates of the indexes of relative risk aversion and relative prudence, as well as the relative preference for the quality of environment suggest marked cross-country heterogeneity.
Keywords: Q50; D81; E21; 330; Consumption; Environmental Risk; Financial Risk; Prudence; Relative Risk Aversion; Relative Preference for the Quality of Environment